1997
DOI: 10.1093/intimm/9.5.645
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G functions as a restriction element and a transplantation antigen in mice

Abstract: HLA-G, a human MHC class I molecule expressed on the trophoblast during pregnancy, was expressed in transgenic mice by recombining the HLA-G gene with a transcriptional promoter from a murine H-2 MHC class I gene. Skin grafts from HLA-G transgenic mice were rejected by non-transgenic mice showing that HLA-G behaves as a xenotransplantation antigen in mice. Further investigation revealed that murine T cells recognize native HLA-G directly as a xenoantigen or they recognize processed peptides derived from HLA-G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…Induction of proliferation in C57BL/6 mouse T cells by crosslinking of Qa-2 had previously been demonstrated [23,[35][36][37][38]. Because only 1% of healthy human T cells express HLA-G protein [44], to perform HLA-G crosslinking experiments on T cells, we used HLA-G transgenic mice on a Qa-2 negative background [45].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of proliferation in C57BL/6 mouse T cells by crosslinking of Qa-2 had previously been demonstrated [23,[35][36][37][38]. Because only 1% of healthy human T cells express HLA-G protein [44], to perform HLA-G crosslinking experiments on T cells, we used HLA-G transgenic mice on a Qa-2 negative background [45].…”
Section: Discussionmentioning
confidence: 99%
“…HLA‐G is a nonclassical MHC‐I molecule that can be expressed as seven isoforms owing to alternative splicing of the primary transcript . Among them, the most studied are membrane‐bound HLA‐G1 and soluble HLA‐G5, both associated to β2m, necessary for their stable conformation . In healthy individuals, HLA‐G tissue distribution is restricted but can be induced under pathological conditions such as organ transplantation, malignant transformation, viral infection, inflammatory and autoimmune diseases .…”
mentioning
confidence: 99%
“…Generation of peptide-specific CTLs. HLA-G transgenic mice (CBA/Ca, H-2 k , H-2K b /HLA-G; hb2m, hCD8a) (Horuzsko et al, 1997) at 6-8 weeks of age were used for experiments. Mice were bred and maintained in a specific-pathogen-free facility at the Medical College of Georgia, GA, USA.…”
Section: Methodsmentioning
confidence: 99%
“…It was proposed that HLA-G on trophoblast cells interacts with several inhibitory or triggering NK cell receptors to protect placental cells against the cytotoxic activity of NK cells (Lanier, 1999). Two reports using HLA-G transgenic mice have demonstrated that HLA-G molecules are recognized as a self-molecule capable of eliciting a cytotoxic T lymphocyte (CTL) response (Horuzsko et al, 1997;Schmidt et al, 1997). In humans, HLA-G expression has been detected also on thymic medullary epithelial cells (Crisa et al, 1997;Mallet et al, 1999) and HLA-G molecules were found to bind CD8a/a with an affinity similar to that observed with classical HLA molecules (Sanders et al, 1991), Human cytomegalovirus (HCMV) infection remains the most common congenital virus infection and is the cause of neurological defects that affect from 0?4 to 2?3 % of liveborn infants (Plotkin, 1994).…”
mentioning
confidence: 99%